Patterns of Sex Chromosome Differentiation in Spiders: Insights from Comparative Genomic Hybridisation - Sember, Alexandr; Pappová, Michaela; Forman, Martin; Nguyen, Petr; Marec, František; Dalíková, Martina; Divišová, Klára; Doležálková-Kaštánková, Marie; Zrzavá, Magda; Sadílek, David; Hrubá, Barbora; Král, Jiří (Genes, 2020)
Spiders are an intriguing model to analyse sex chromosome evolution because of their peculiar multiple X chromosome systems. Y chromosomes were considered rare in this group, arising after neo-sex chromosome formation by X chromosome-autosome rearrangements. However, recent findings suggest that Y chromosomes are more common in spiders than previously thought. Besides neo-sex chromosomes, they are also involved in the ancient X1X2Y system of haplogyne spiders, whose origin is unknown. Furthermore, spiders seem to exhibit obligatorily one or two pairs of cryptic homomorphic XY chromosomes (further cryptic sex chromosome pairs, CSCPs), which could represent the ancestral spider sex chromosomes. Here, we analyse the molecular differentiation of particular types of spider Y chromosomes in a representative set of ten species by comparative genomic hybridisation (CGH). We found a high Y chromosome differentiation in haplogyne species with X1X2Y system except for Loxosceles spp. CSCP chromosomes exhibited generally low differentiation. Possible mechanisms and factors behind the observed patterns are discussed. The presence of autosomal regions marked predominantly or exclusively with the male or female probe was also recorded. We attribute this pattern to intraspecific variability in the copy number and distribution of certain repetitive DNAs in spider genomes, pointing thus to the limits of CGH in this arachnid group. In addition, we confirmed nonrandom association of chromosomes belonging to particular CSCPs at spermatogonial mitosis and spermatocyte meiosis and their association with multiple Xs throughout meiosis. Taken together, our data suggest diverse evolutionary pathways of molecular differentiation in different types of spider Y chromosomes.
Keywords: Arthropoda; Sex Chromosomes; Male; pohlavní chromozomy; repetitive DNA; neo-sex chromosome; srovnávací genomová hybridizace; karyotype evolution; achiasmatic pairing; in situ hybridisation; karyotyp; Meiosis; biologická evoluce; mužské pohlaví; X1X20; Spiders; genom; meióza; Animals; Y chromosome; ženské pohlaví; pavouci; Biological Evolution; Sex Differentiation; X1X2Y; male-specific region; zvířata; Comparative Genomic Hybridization; sexuální diferenciace; Genome; Female; Karyotype